Experimental study of local shear strain remotely induced by pulsed ultrasound in tissue-mimicking phantoms - Barannik, E.; Girnyk, S.; Tovstiak, V.; Marusenko, A; Volokhov, V. (Biophysical Bulletin, 2018)
The present study revealed the significant dependence of displacement magnitude and strain relaxation on phantom elasticity and viscosity. It has been shown that simultaneous analysis of temporal behavior and magnitude of shear strain induced by the radiation force of focused ultrasonic beam gives the necessary data for quantitative estimation of tissue viscosity and shear modulus due to the known functional dependencies of displacements on these parameters. As a result the simplest calibration procedure of acoustic radiation force based methods is performed for used excitation beam. These findings were tested, in particular, using data obtained for specially prepared phantoms containing calf liver and muscle tissue in vitro. The observed complex character of shear strain relaxation in some tissue phantoms and tissues in vitro reduces the preciseness of viscoelastic properties estimation.